Implementation of School Co-Curricular Activities through the Saturday Program (PROSA) - Rujiani Rujiani; Sarwi Sarwi; Ani Rusilowati (Proceedings of International Conference on Science, Education, and Technology, 2026)
The Saturday Program (PROSA) at SD Negeri Tlogowungu 02 is a co-curricular innovation designed to support 21st-century educational transformation. This program responds to the school’s limited resources, small number of students, and need for more contextual, meaningful, and character-building learning experiences. PROSA is conducted every Saturday through five rotating activities: Sarijo, Sariman, Sarijan, Sadolan, and Saguta. These activities integrate healthy living habits, environmental awareness, gardening, entrepreneurship, and career introduction through the involvement of teachers, students, parents, and the local community. The program applies a Deep Learning approach based on the principles of honoring students, awareness, meaningful learning, and joyful learning. Assessment is carried out formatively and summatively through observation, reflection journals, portfolios, documentation, student products, and feedback from parents and the community. The implementation results show that PROSA improves students’ responsibility, collaboration, creativity, independence, healthy living awareness, environmental care, and entrepreneurial skills. The program also strengthens partnerships among the school, families, and the community. However, the use of technology and parental participation still need further improvement. Overall, PROSA can serve as a relevant co-curricular model for developing students’ competencies holistically in elementary schools.